Subjective method for tracheal tube cuff inflation: performance of anesthesiology residents and staff anesthesiologists. Prospective observational study - Duarte,Nádia Maria da Conceição (2020)
Abstract Background and objectives: Poor monitoring of tracheal tube cuff pressure may result in patient complications. The objective method of using a manometer is recommended to keep safe cuff pressure values (20‒30 cm H2O). However, as manometers are not readily available, anesthesiologists use subjective methods. We aimed to assess appropriateness of a subjective method for attaining cuff pressure and the expertise level of manometer handling among anesthesiology staff and residents in a university teaching hospital. Methods: Prospective observational study, recruiting participants that performed tracheal intubation and the subjective method for tube cuff inflation. Patients with difficult airway, larynx and trachea anatomic abnormality and emergency procedures were not included. Up to 60 minutes after tracheal intubation, an investigator registered the cuff pressure using an aneroid manometer (AMBU®) connected to the tube pilot balloon. Results: Forty-seven anesthesiologists were included in the study - 24 residents and 23 staff. Mean (SD) and medians (IQR) measured in cmH2O were, respectively, 52.5 (27.1) and 50 (30‒70). We registered 83% of measurements outside the recommended pressure range, with no difference between specialists and residents. The level of expertise with the objective method was also similar in both groups. Pressure adjustments were performed in 76.6% of cases. Conclusion: The subjective method for inflating the tracheal tube cuff resulted in a high rate of inadequate cuff pressures, with no difference in performance between anesthesiology specialists and residents.